Speeding up the Stress Analysis of Hollow Circular FGM Cylinders by Parallel Finite Element Method - S. Asil Gharebaghi; N. Niknam (Numerical Methods in Civil Engineering)
In this article, a parallel computer program is implemented, based on Finite Element Method, to speed up the analysis of hollow circular cylinders, made from Functionally Graded Materials (FGMs). FGMs are inhomogeneous materials, which their composition gradually varies over volume. In parallel processing, an algorithm is first divided to independent tasks, which may use individual or shared data. Such tasks could be simultaneously executed. In this paper, a parallel Finite Element software is developed to perform the analysis on a multiprocessor system. The software parallelizes every time-consuming task of the algorithm, if possible. As an application, the analysis of a thick hollow cylinder, made from FGM, is performed to evaluate the capability of the software. The results show not only the software is authoritative of analyzing large-scale problems, but also it is 2.4 times faster than the serial version. Although such speedup is achieved using eight processors, the number of processors could be increased utilizing computer networks. According to the results, it could be concluded that the speedup increases when the number of processors increases. However, because of some technical limits and overheads such as data traffic among the processors, the speedup approaches its maximum for a certain number of processors.